STUDI PERBAIKAN CARA PENYADAPAN KOPAL DI KPH SUKABUMI - Soenarno Soenarno; Maman Mansyur Idris; Zakaria Basari (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
Copal from Agathis tree has been one of  important  forest  products, not only as export commodity but also as raw material for some induatries. In the last few years however production  in  this country  began to decrease, due to inefficient  tapping by the forest worker.